2022
DOI: 10.1101/2022.10.25.22281458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blood-Based Transcriptomic and Proteomic Biomarkers of Emphysema

Abstract: Rationale: Emphysema is a key component of COPD with important prognostic implications. Identifying blood-based biomarkers of emphysema will facilitate early diagnosis and possible development of targeted therapies. Objectives: Discover blood transcriptomic and proteomic biomarkers for chest computed tomography-quantified emphysema in smokers and develop predictive biomarker panels. Methods: Emphysema blood biomarker discovery was performed using differential gene expression, alternative splicing, and protein … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 95 publications
1
4
0
Order By: Relevance
“…We also developed machine learning predictive models for emphysema using transcriptomic and proteomic biomarkers. Some of these results have been previously reported as an abstract (29) and a preprint (30).…”
Section: Introductionsupporting
confidence: 60%
“…We also developed machine learning predictive models for emphysema using transcriptomic and proteomic biomarkers. Some of these results have been previously reported as an abstract (29) and a preprint (30).…”
Section: Introductionsupporting
confidence: 60%
“…In a study reported in this issue of the Journal , Suryadevara and colleagues (pp. 273–287 ) took advantage of available data from the two large COPDGene (Genetic Epidemiology of COPD) and ECLIPSE (Evaluation of COPD Longitudinally to Identify Predictive Surrogate End-Points) cohorts ( 5 ). The authors show that a multiomics approach in blood allows the identification of genes, proteins, gene isoforms, and exons relevant to COPD that could not be identified smaller studies using sometimes more relevant tissues.…”
mentioning
confidence: 99%
“…Another important aspect of the study by Suryadevara and colleagues ( 5 ) is the focus on emphysema as a continuous trait rather than investigating the heterogeneous group of patients with COPD overall. Thus far, only a few studies have investigated the underlying molecular mechanisms of emphysema using genomewide data, most of them using single-omics approaches with an assessment of the presence of emphysema rather than analyzing the trait as a continuous variable ( 2 , 6 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations